Food consumption during recession: the case of Italy in the period 2001-2013 - Zuppiroli, Marco (Progress in Nutrition, 2015)
Italian families, affected by the recession, have reduced consumption not only in terms of expenditure, but also on the amount of goods and services purchased. The analysis shows that expenditure, in real terms, for food and beverages fell by -21 percent in 2007-2013; contraction in 2001-2007, always net of price dynamics, was found to -5 percent only. The food can reduce spending through its recomposition favoring merchandise less “rich” and processed within the different food categories. The affirmation of a style marked by purchasing savings depends not only upon the constraints dictated by the family budget, but also by ethical values that inspire respect for the environment and sustainability and that helped to increase the consumption of organic products in contrast to the food expenditure as a whole.